1998
DOI: 10.1074/jbc.273.14.8040
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of d-Lactate Dehydrogenase to the Inner Membrane of Mitochondria

Abstract: Nuclear encoded proteins of the inner membrane of mitochondria contain topogenic signals which function to sort them to the membrane following their import. These topogenic signals comprise hydrophobic cores of varying length and are flanked usually by charged amino acids. In many instances these signals form integral parts, the transmembrane anchors, of the sorted protein. In a small number of cases they are proteolytically cleaved following the sorting event. These topogenic signals are distinct from mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…A similar behavior upon alkaline treatment of mitochondria was observed for D-lactate dehydrogenase (Fig. 2B), a protein that is anchored to the inner membrane by a single N-terminal transmembrane segment and faces the intermembrane space (29). In contrast, the ADP/ ATP carrier (Aac2), an integral membrane protein with six membrane-spanning segments (27), was completely resistant to extraction by carbonate (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…A similar behavior upon alkaline treatment of mitochondria was observed for D-lactate dehydrogenase (Fig. 2B), a protein that is anchored to the inner membrane by a single N-terminal transmembrane segment and faces the intermembrane space (29). In contrast, the ADP/ ATP carrier (Aac2), an integral membrane protein with six membrane-spanning segments (27), was completely resistant to extraction by carbonate (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Such an arrangement is present in a variety of mt inner membrane proteins. In the case of D-lactate dehydrogenase, which attains a similar N in -C out orientation in the inner membrane, it was shown that the TM segment and the following cluster of charged aa act as a bipartite sorting signal (Rojo et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [10,16,17] have shown that the presence of charged residues in the neighborhood of a transmembrane domain can affect membrane integration in the mitochondrial inner membrane. Consistent with this, statistical analysis on the distribution of charged residues flanking the transmembrane domains of mitochondrial inner membrane proteins that follow the 'stop-transfer' pathway has shown that positively charged Lys and Arg residues are abundant on both sides of the TM segments, whereas negatively Fig.…”
Section: Resultsmentioning
confidence: 99%